Monitoring and evaluation of the results of the implementation of the crm system ("Journal "U". Economy. Management. Finance.", 2023)
The article presents an algorithm for evaluation of the result of implementation of the CRM system, the concept of a CRM-system is given, a scheme for monitoring the results of its implementation is proposed. It also shown indicators of customer relationships and sales indicators, according to which you can later draw conclusions about the success of the system, make decisions about setting up business processes or CRM modules. The influence of CRM on support team is considered separately.
Keywords: CRM; monitoring; customer relationship; sales performance; support; quality assessment; leads; customer satisfaction